Eksistensi Pengadilan Pajak dalam Sistem Peradilan di Indonesia Pasca Putusan Mahkamah Konstitusi Nomor 26/PUU-XXI/2023 - Abdillah; Hartati; Sarwani, Raden (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This article examines the existence of the Tax Court within the Indonesian judicial system following Constitutional Court Decision Number 26/PUU-XXI/2023. The transfer of authority over the Tax Court to the Supreme Court constitutes a significant structural reform in the tax judiciary aimed at strengthening the principle of judicial independence. Previously, the implementation of a dual-roof system created a potential conflict of interest because the Ministry of Finance, as part of the executive branch, continued to control the non-technical aspects of the Tax Court, which could affect the independence of judges in adjudicating tax disputes. This condition contradicts the principle of an independent judiciary as stipulated in Article 24 paragraphs (1) and (2) of the 1945 Constitution. This study employs a normative legal research method using statutory and conceptual approaches to formulate an ideal regulatory framework for the institutional structure of the Tax Court in Indonesia. The findings indicate that the current position of the Tax Court is not fully aligned with the one-roof judicial system mandated by the Constitution. Therefore, a comprehensive institutional restructuring is necessary to ensure the Tax Court becomes an integral part of judicial power, including institutional strengthening at the provincial level to guarantee faster and more equitable access to justice for taxpayers.